IS/IT STRATEGIC PLANNING PADA PERUSAHAAN MONO JAYA CILACAP JAWA TENGAH - Setiawan, Ito; Rahmawati, Anjar Sylvia; Hariawan, Akto (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2020)
At present business competition in Indonesia is getting tougher, including business competition in the field of wig making. PT Mono Jaya is one of the companies engaged in the production of wigs that are in Kroya, Cilacap district, Central Java. To increase competitiveness against its competitors, companies must be able to create new innovations and use information systems that are in accordance with the needs of the company as a support to improve performance, increase competitiveness against its competitors, and realize the company's goals. But to get an information system that fits the needs of the company, it requires an information system strategic planning. This study uses the Ward And Peppard method, the tools used are SWOT analysis, Value Chain analysis, McFarlan Strategic Grid analysis, Five Force Porter Model analysis, Critical Success Factor (CSF) analysis, and Balaced ScoreCard (BSC) analysis. The final results of this study are in the form of information system portfolio recommendations that are needed by PT Mono Jaya to improve the competitiveness of the company